2012
DOI: 10.1159/000334642
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Magnifying Narrow-Band Imaging Endoscopy for the Diagnosis of Gastric and Colorectal Lesions

Abstract: A series of studies about the potential usefulness of magnifying endoscopy with narrow-band imaging (NBI) for the diagnosis of gastric and colonic lesion is reviewed. Concerning the magnifying NBI appearances of gastric lesions, a light blue crest is a highly accurate sign of the presence of histological intestinal metaplasia. Also, the degree of irregularity of the mucosal and vascular pattern is correlated with the histological severity of Helicobacter pylori-associated chronic gastritis. According to the ‘V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…The last trials showed that the recurrence rates increased from 4% at 3 mo to 32% at 1 yr for NBI-TUR and from 12% to 51% for WLI-TUR. Because of the increasing trend of tumor recurrence, some recurrence is attributed to causes other than missed tumors, such as the field cancerization effect [35] or the clonal origin of urothelial cancer [13], which are not yet completely understood. The recurrence mechanism of NMIBC should be further studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The last trials showed that the recurrence rates increased from 4% at 3 mo to 32% at 1 yr for NBI-TUR and from 12% to 51% for WLI-TUR. Because of the increasing trend of tumor recurrence, some recurrence is attributed to causes other than missed tumors, such as the field cancerization effect [35] or the clonal origin of urothelial cancer [13], which are not yet completely understood. The recurrence mechanism of NMIBC should be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…NBI improves tumor visibility by enhancing the contrast between vascularized lesions and normal mucosal [1012]. These features allow NBI to detect small or flat early tumors that are difficult to observe by WLI [13]. Systems integrating both NBI and WLI are already available.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the contrast between urothelial carcinomas (UCs) and normal urothelium is enhanced by NBI, allowing for the detection of UCs more easily. This feature is particularly noticeable for small or flat early UCs, which conventional WLI struggles to detect (2).…”
Section: Introductionmentioning
confidence: 97%
“…Magnifying endoscopy combined with narrow band imaging (ME-NBI) enables a clear visualization of the microvascular architecture and the microsurface structure of the superficial section of the mucosa. Certain studies have demonstrated that ME-NBI findings are closely associated with the histological type of gastric mucosal lesion (2,(6)(7)(8)(9). In particular, irregularities of microstructures have been revealed to be crucial for the endoscopic diagnosis of early gastric cancer (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%